2020
DOI: 10.21203/rs.3.rs-36676/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

EvoMol: a flexible and interpretable evolutionary algorithm for unbiased de novo molecular generation

Abstract: The objective of this work is to design a molecular generator capable of exploring known as well as unfamiliar areas of the chemical space. Our method must be flexible to adapt to very different problems. Therefore, it has to be able to work with or without the influence of prior data and knowledge. Moreover, regardless of the success, it should be as interpretable as possible to allow for diagnosis and improvement. We propose here a new open source generation method using an evolutionary algorithm to sequ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
(34 reference statements)
1
6
0
Order By: Relevance
“…4 have low values, less than 2.5, suggesting that they are readily synthesizable. It is noticeable that, even though we optimized in this study, the values of the top-12 molecules are identical or comparable to the best reported values obtained from the sole optimization of [ 26 ]. In conclusion, the above results indicate that molecule optimization of using MolFinder successfully generated a set of molecules with good drug-likeness and synthetic accessibility simultaneously.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…4 have low values, less than 2.5, suggesting that they are readily synthesizable. It is noticeable that, even though we optimized in this study, the values of the top-12 molecules are identical or comparable to the best reported values obtained from the sole optimization of [ 26 ]. In conclusion, the above results indicate that molecule optimization of using MolFinder successfully generated a set of molecules with good drug-likeness and synthetic accessibility simultaneously.…”
Section: Resultssupporting
confidence: 82%
“…Most existing GA-based molecular optimization algorithms are based on the graph representation of a molecule. In recent studies, they showed competitive, sometimes better, performance compared to ML-based methods in generating novel molecules with desired properties [ 26 , 27 , 29 , 30 ]. In addition, the design of any arbitrary operation may be limited because generally it is tightly coupled with the molecular manipulation functionality of underlying cheminformatics libraries, such as RDKit [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is noticeable that, even though we optimized S mQED in this study, the S QED values of the top-12 molecules are identical or comparable to the best reported values obtained from the sole optimization of S QED . 25 In conclusion, the above results indicate that molecule optimization of S mQED using MolFinder successfully generated a set of molecules with good drug-likeness and synthetic accessibility simultaneously. This clearly demonstrates that MolFinder can help accelerate the drug discovery process by generating novel drug candidates that are readily synthesizable.…”
Section: Optimization Of Drug-likenessmentioning
confidence: 67%
“…In addition to recent ML-based approaches, various genetic algorithm (GA)-based molecular property optimization algorithms have been developed. [25][26][27][28][29][30][31][32][33] The main advantage of GA-based algorithms is that they do not require a large amount of molecule data relevant to a given optimization task because they search novel molecules in a combinatorial and stochastic way. Also, they do not need to train a molecule generator, which takes considerable computational time and resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation